Algoritma Incremental Conductance dan Perturbation Observation Sebagai Kendali MPPT PLTS 1000Wp - Handoko Rusiana Iskandar; Yuda Bakti Zainal; Susanto Sambasri; M. Haris Yogi Ernanda (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2020)
Nowadays, electricity consumption in Indonesia still rising the future, as fuel cell energy reserves continue to decline, this has pushed people to switch to new and renewable energy which guarantees the availability of new electricity sources. A Photovoltaic system has been installed in the Electrical Engineering Laboratory with a capacity of 1 kWp. The PV system is proposed as a new source of electricity to support the electricity needs of laboratories other than PLN. This paper compares the modeling that has been done using the Maximum power point tracking (MPPT) algorithm namely Incremental Conductance (IC) and Perturbation & Observation (P&O) in Standard Test Condition (STC) of 1000 W/m2 and a temperature of 25ËšC. The control simulation of the MPPT DC / DC Boost Converter is calibrated to satisfy the 220V/50 Hz PLN grid. The simulation results the MPPT control with the P&O algorithm has output power of 960 W and an efficiency of 99,9 % when using the IC process has 944 W and an efficiency of 98,7%. The P&O was selected to have optimum performance relative to the IC approach in the 1000 Wp PLTS system in the Electrical Engineering Laboratory.